Improving multi-agent systems using Jason - Vester, Steen; Boss, Niklas Skamriis; Jensen, Andreas Schmidt; Villadsen, Jørgen (Annals of mathematics and artificial intelligence, 2011)
We describe the approach used to develop the multi-agent system of herders that competed as the Jason-DTU team at the Multi-Agent Programming Contest 2010. We also participated in 2009 with a system developed in the agent-oriented programming language Jason which is an extension of AgentSpeak. We used the implementation from 2009 as a foundation and therefore much of the work done this year was on improving that implementation. We present a description which includes design and analysis of the system as well as the main features of our agent team strategy. In addition we discuss the technologies used to develop this system as well as our future goals in the area.